2014
DOI: 10.5614/j.math.fund.sci.2014.46.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Haze Problems in the North of Thailand using Logistic Regression

Abstract: At present, air pollution is a major problem in the upper northern region of Thailand. Air pollutants have an effect on human health, the economy and the traveling industry. The severity of this problem clearly appears every year during the dry season, from February to April. In particular it becomes very serious in March, especially in Chiang Mai province where smoke haze is a major issue. This study looked into related data from 2005-2010 covering eight principal parameters: PM 10 (particulate matter with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Lalitaporn et al [26] found high concentrations of NO2 in Chiang Mai during biomass burning season of March-April which agreed well with PM10 and CO concentrations. Similarly, Pimpunchat et al [33] presented high concentrations of PM10 during March-April in Chiang Mai owing to haze situation. They also reported high correlation of PM10 concentrations versus NO2, CO, and O3 concentrations.…”
Section: Introductionmentioning
confidence: 88%
“…Lalitaporn et al [26] found high concentrations of NO2 in Chiang Mai during biomass burning season of March-April which agreed well with PM10 and CO concentrations. Similarly, Pimpunchat et al [33] presented high concentrations of PM10 during March-April in Chiang Mai owing to haze situation. They also reported high correlation of PM10 concentrations versus NO2, CO, and O3 concentrations.…”
Section: Introductionmentioning
confidence: 88%
“…The data collected were subsequently analyzed using the path modeling technique, utilizing SPSS as a tool for data analysis. (Pimpunchat, Sirimangkhala, & Junyapoon, 2014;Taro, 1973).…”
Section: Methodsmentioning
confidence: 99%
“…Many researchers used their national AQI to identify class for their classification model (P. Perez & Reyes, 2006;Díaz-Robles et al, 2008;Stadlober et al, 2008;P. Perez, 2012;Sabri & Tarek, 2012;Pimpunchat et al, 2014;Fu et al, 2015;Saithanu & Mekparyup, 2015b, 2015cFaganeli Pucer et al, 2018;Srijiranon & Eiamkanitchat, 2018 Apart from the aforementioned outputs, a small number of research reported average values between monitoring stations, the likelihood of pollution to enter hazardous levels, and the differences between daily and annual average air quality.…”
Section: Output Datamentioning
confidence: 99%
“…This method was generally implemented to find relationships between input features and PM 10 . Many researchers calculate the r value, then select only input features that passed specific thresholds (García Nieto et al, 2018b;Liu et al, 2015;Mekparyup & Saithanu, 2013Pimpunchat et al, 2014;Saithanu & Mekparyup, 2015a, 2015b, 2015cTaşpınar, 2015).…”
Section: Features Selectionmentioning
confidence: 99%